Implementation of PR Marketing Strategy in Marketing OmJeckBelitang - Evi Antika; Anggalia Wibasuri (Proceeding International Conference on Information Technology and Business, 2020)
The OmJeckBelitang application was introduced to the East OKU community so that people can experience the benefits of technology by using a technology-based online motorcycle taxi application. In addition to providing transportation motorcycle taxi services, OmJeck is also working to develop applications with various features including JeckFood, FoodDrinks, JeckBlanja, JeckMo, Education, OmCar, and JackAgro. In this study, this application provided a system to helps in refilling regular credit, internet credit and electricity tokens. The payment system in this application was also accessed using OVO, Dana, and LinkAja. It was important to implement a public relations marketing strategy to facilitate the achievement of company goals. As for the marketing public relations strategy, there were three types of strategies, namely the Pull Marketing Public Relations Strategy, the Push Marketing Public Relations Strategy, and the Pass Marketing Public Relations Strategy.Keywords: Marketing Public Relations, Pull Strategy, Push, Pass, OmJeckBelitang